The impact of a career development programme on the career self-efficacy and academic motivation of grade 11 learners from diverse socio-economic backgrounds - Miles, Jean (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015